Desigualdad, inflación, ciclos y crisis en Chile - Pablo García; Camilo Pérez N. (Estudios de Economía, 2017)
– We analyze the effects of macroeconomic fluctuations, as well as episodes of financial instability and inflation, on inequality indicators in Chile for the period 1960-2014. The relationship between episodes of crisis and fluctuations on levels of inequality are estimated from an event study, finding that they are related to fluctuations in inequality. In addition, we perform econometric estimates where inequality indicators relate to different macroeconomic variables and educational performance. The main conclusions are that banking and inflation crises, as well as periods of severe cyclical contractions, tend to increase the levels of inequality in Chile.
Keywords: E30; I30; D31; 330; Economic crisis; inequality; income distribution